The Principles of Service-Orientation. - Erl, Thomas (SOA webservices journal.)
With the unwavering prominence of service-oriented architecture (SOA) there is an increasing interest in understanding what exactly it means for something to be considered "service-oriented." Thomas Erl recently completed a lengthy research project for SOA Systems Inc., into the origins of SOA and the current state of service-orientation among all primary SOA technology platforms. This body of work contributed to the mainstream SOA methodology developed by SOA Systems and was also documented in Thomas's new book, Service-Oriented Architecture : Concepts, Technology, and Design. We caught up with Thomas (a previous contributor to WSJ) to ask him to share some of the insights he gained from his work with SOA and service-orientation.